Numerical algorithms for simulation of multisection lasers by using traveling wave model - Čiegis, Raimondas; Radziunas, Mindaugas; Lichtner, Mark (Mathematical Modelling and Analysis, 2008)
Sequential and parallel algorithms for the simulation of the dynamics of high‐power semiconductor lasers is presented. The model equations describing the multisection broad–area semiconductors lasers are solved by the finite difference scheme, which is constructed on staggered grids. This nonlinear scheme is linearized applying the predictor‐corrector method. The algorithm is implemented by using the ParSol tool of parallel linear algebra objects. For parallelization we adopt the domain partitioning method, the domain is split along the longitudinal axis. Results of computational experiments are presented, the obtained speed‐up and efficiency of the parallel algorithm agree well with the theoretical scalability analysis.First Published Online: 14 Oct 2010